Representações de docentes sobre as sexualidades da pessoa com síndrome de down - Nantes, Elaine da Silva (2018)
This study aimed to characterize the social representations of the mothers-teachers and their children, aged from 4 to 6 years-old, concerning the ways of educating. The study is part of the productions of the research group in School, Family and Society (GEPEFS). As a contribution to group studies, is justified by the need to understand how the educational practices adopted by the families are understood by the children, therefore to contribute to families in the sense that leads them to seek constant dialogue as a way of establishing a relationship of trust and affection when reprimanding a behavior understood as inappropriate. As a theoretical-methodological support, we chose the Theory of Social Representations that assisted us in understanding the thoughts and values that permeate the imagination of mothers and children when it comes to educating. The theory investigates the formation and the functioning of the reference systems we use to classify and interpret everyday events, as well as what happens within families. Ten mothers, who work as kindergarten teachers at a private school in a city located on the north of Paraná, as well as their ten children, between the ages of 4 and 6 years-old, participated on the study. The research proposal was: what are the social representations of mothers-teachers and their children about ways of educating? In order to carry out the research with the mother-teachers, the following instruments were used: a) Sociodemographic questionnaire; b) Free Word Association Test; c) Semistructured Interview Guideline. To collect data with the children, the following instruments were used: a) Free Word Association Test; b) Semistructured Interview Guideline; c) Guideline with questions regarding children's drawings. The research?s nature is qualitative. The results reveal that the social representations of the majority of mothers-teachers about the ways of educating come from the memories and influences of the way they were educated. Although they try to understand that the social and cultural changes occurred in family, with the insertion of women in the work field and increasingly assuming the position of responsible for the family base, mothers still seek as a reference the way in which they were educated to educate their own children. On the other hand, the social representations of the children on the ways of educating show us that adults often punish the children, without knowing if they understand why they are grounded or punished. When asked about how they will educate their children, in case they have them, the interviewed children are in favor of offering an affectionate home, with much love and care, showing that affective dialogue is always the best condition of proximity and understanding of the other. We have concluded that, even without realizing it, some mothers-teachers reproduce in the relationship with their children the ways of educating received from their mothers. In this way, they anchor their representations about the ways of educating in beliefs coming from the families in which they were inserted, preventing them from discovering their own way of doing so